Analisis Diskriminan Untuk Memprediksi Kebangkrutan Perusahaan: Studi Kasus Pada Perusahaan Sektor Textile Dan Garment Di Bursa Efek Indonesia 2016-2018 - Deny Ismanto; Dyah Ernawati (Jurnal Sains Sosio Humaniora, 2021)
Failure to make a continuous profit will hamper the company's development and this can lead to bankruptcy. Bankruptcy is usually marked by financial distress. Companies that are not able to overcome financial difficulties and problems are getting protracted, then the company will go bankrupt. One way to predict bankruptcy is by using discriminant analysis. This type of research is descriptive with a quantitative approach. The data collection method used is documentation. The population in this study were Textile & Garment companies listed on the IDX in 2016-2018. The sampling technique was purposive sampling and obtained a sample of 8 companies with a potential bankruptcy and 10 companies for 3 years of observation. The results showed that of the 2 financial ratios used Quick Ratio (QR) and Return On Asset (ROA), only the Quick Ratio (QR) ratio proved significant to be able to distinguish bankrupt and non-bankrupt companies. By using discriminant analysis. The dominant variable informing the discriminant function is the Quick Ratio (QR).